Significance of numerical chromosome abnormalities in children with acute leukaemias detected by flow cytometry - Pierzyna-Świtała, Magdalena; Sędek, Łukasz; Mazur, Bogdan (Pediatria Polska - Polish Journal of Paediatrics, 2018)
Acute leukaemias (AL) constitute a heterogeneous group of diseases that differ in terms of immunophenotype, as well as structural and numerical chromosome alterations. In recent years research has revealed many genetic abnormalities in leukaemic cells. Some of them have already well-grounded diagnostic and prognostic significance in acute lymphoblastic leukaemia (ALL) and play an important role in patient risk stratification. Besides cytogenetics, which still remains a gold standard for the classification of AL, also flow cytometry can be useful in detecting abnormal numbers of chromosomes in leukemic blasts. The presence of DNA aneuploidy may be an early indicator of cytogenetic abnormality directly associated with response to therapy. High hyperdiploidy with 51–65 chromosomes and DNA index > 1.16 is a favourable prognostic factor in ALL in children, often related to CD123 antigen overexpression. The aim of this study was to summarise current knowledge about numerical chromosome abnormalities in AL diagnosed by flow cytometry.